Design and analysis of clinical nursing research studies - Martin, Colin R., 1964- (Routledge essentials for nurses., 2000)
This text covers all aspects of the design and statistical analysis of clinical research studies. Clinical research material is used throughout the volume to illustrate the design types and statistical tests used.